2021
DOI: 10.1186/s12888-021-03591-7
|View full text |Cite|
|
Sign up to set email alerts
|

How best to provide help to bereaved adolescents: a Delphi consensus study

Abstract: Background Many adolescents struggle with their grief and mental health issues after the death of a close person, such as a family member or a friend. Given the potentially devastating impact of the loss on the adolescent and their family, professional help can be warranted. However, little is known about how to best help these adolescents. This study aimed to address this gap by determining what help professionals (i.e., counselors) should provide to bereaved adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Author details 1 Centre for Mental Health, Melbourne School of Population and Global Health, The University of Melbourne, 207 Bouverie St., Carlton, VIC 3053, Australia. 2 Faculty of Health, University of Canberra, Bruce ACT , Canberra 2617, Australia.…”
Section: Open Accessmentioning
confidence: 99%
“…Author details 1 Centre for Mental Health, Melbourne School of Population and Global Health, The University of Melbourne, 207 Bouverie St., Carlton, VIC 3053, Australia. 2 Faculty of Health, University of Canberra, Bruce ACT , Canberra 2617, Australia.…”
Section: Open Accessmentioning
confidence: 99%
“…These findings are in line with review of the literature and consensus recommendations, indicating that a parental or family component may contribute to effectiveness of support offered to children and adolescents bereaved by suicide. 11 Overall, studies have reported mixed findings regarding the effectiveness of postvention interventions, and especially the effectiveness of interventions in regard to risk for suicidal ideation and behaviour remains unclear, mostly because of a lack of research. 12 Nonetheless, a few family-oriented studies reported on suicidal ideation as an intervention outcome.…”
Section: Postventionmentioning
confidence: 99%
“…These findings are in line with review of the literature and consensus recommendations, indicating that a parental or family component may contribute to effectiveness of support offered to children and adolescents bereaved by suicide. 11 …”
Section: Postventionmentioning
confidence: 99%
“…Many people need professional and often long-term follow-up to go on with their own lives. [14][15][16] Adolescents who have been followed up by professionals emphasize the time aspect: They may need more help in the long term rather than immediate help after the suicide. 16 Family members report the importance of not feeling alone, especially during the critical period after the suicide.…”
Section: Introductionmentioning
confidence: 99%